2012
DOI: 10.1101/gad.179804.111
|View full text |Cite
|
Sign up to set email alerts
|

A decade of 3C technologies: insights into nuclear organization

Abstract: Over the past 10 years, the development of chromosome conformation capture (3C) technology and the subsequent genomic variants thereof have enabled the analysis of nuclear organization at an unprecedented resolution and throughput. The technology relies on the original and, in hindsight, remarkably simple idea that digestion and religation of fixed chromatin in cells, followed by the quantification of ligation junctions, allows for the determination of DNA contact frequencies and insight into chromosome topolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
491
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 657 publications
(496 citation statements)
references
References 99 publications
(123 reference statements)
4
491
0
1
Order By: Relevance
“…It appears that the enhancer loops form prior to gene activation and stably associate with paused RNAPII at promoters, keeping this loop topology ready for rapid activation of transcription by recruitment of additional factors [116]. The formation of chromatin loops brings the enhancer and its target promoter into close physical proximity in the nucleus and this feature is utilised by chromatin conformation capture experimental approaches [117] to detect long-range interactions genomewide [118] and to identify target promoters of specific regulatory elements. However, the knowledge about the specificity of promoter-enhancer interactions is still very limited.…”
Section: Diverse Promoter Architectures Enable Complex Regulatory Lanmentioning
confidence: 99%
“…It appears that the enhancer loops form prior to gene activation and stably associate with paused RNAPII at promoters, keeping this loop topology ready for rapid activation of transcription by recruitment of additional factors [116]. The formation of chromatin loops brings the enhancer and its target promoter into close physical proximity in the nucleus and this feature is utilised by chromatin conformation capture experimental approaches [117] to detect long-range interactions genomewide [118] and to identify target promoters of specific regulatory elements. However, the knowledge about the specificity of promoter-enhancer interactions is still very limited.…”
Section: Diverse Promoter Architectures Enable Complex Regulatory Lanmentioning
confidence: 99%
“…7 Using the Hi-C approach, Lieberman-Aiden and colleagues have demonstrated that in mammals, transcriptionally active and inactive regions of the genome are spatially segregated within the 3D nuclear space, forming A and B compartments, respectively. 8 Both compartments appear to be partitioned into megabase-and sub-megabase-scale topologically-associating (self-interacting) domains (TADs).…”
Section: Hierarchical Folding Of the Eukaryotic Genome Within The Celmentioning
confidence: 99%
“…This organization is an emerging area of importance, as the function and activity of loci are strongly correlated with their 3D conformations 1,2 . To explore such chromosome interactions at a genome-wide level, chromosome conformation capture (3C)-based high-throughput methods, in particular Hi-C, have been extensively used [3][4][5] . Hi-C measures pairwise contact frequencies between all loci in the genome using populations of millions of cells.…”
Section: Introductionmentioning
confidence: 99%
“…Hi-C measures pairwise contact frequencies between all loci in the genome using populations of millions of cells. These data have led to advances in the understanding of higher-order organization of the genome, such as chromatin loop formation and the discovery of topologically associating domains [6][7][8] , and they have been used to build 3D models of chromatin 3,9,10 . However, it is important to note that Hi-C data represent an ensemble average of millions of cells, and decades of microscopy studies have shown that nuclear organization is not uniform, even among cells of a homogeneous population 11 .…”
Section: Introductionmentioning
confidence: 99%